Startup Stations: The Impact of Rail Access on Entrepreneurship (Self-Employment) in England Wales - Rosa Sanchis-Guarner; Nikodem Szumilo; Antoine Vernet (CESifo GmbH, 2024)
We study the impact of improved rail access on entrepreneurship rates in England and Wales. We use data from the Census spanning 2001, 2011, and 2021 to analyse self-employment rates in granular geographic areas of around 200 residents. Specifically, we study how they respond to changes in the distance to the nearest train station occurring due to 56 new station openings. We find that all else equal, moving 1 km further away from a station reduces self-employment rates by 0.12 percentage points, with the effect dissipating beyond 7 km. Secondary results suggest that access to rail makes it easier to become self-employed while not making it more attractive compared to employment. Our findings suggest that rail infrastructure improvements can support local entrepreneurship and economic activity, contributing to regional development and reducing economic inequality.
Keywords: L26; O18; R11; 330; entrepreneurship; rail; self-employment